Media Literacy in the K-12 Classroom, 2nd Edition - Baker, Frank W. (Book collections on Project MUSE., 2016)
Today's average youth spends over 10 hours a day consuming media. Aided by technology, young people can instantly share and engage with media messages to find answers, get directions, shops or connect with friends. But access alone doesn't lead to critical thinking. Media are texts, designed to be read, analyzed, deconstructed and reconstructed. Understanding how to interpret advertising messages, check for bias or avoid stereotyping are among the skills students need to become knowledgeable consumers and producers of media. This book helps educators understand the importance of teaching media literacy and gives them the tools needed to bring this form of literacy into the classroom. Included in this new edition:" n appendix with over 80 author-recommended resources." nsights from respected educators and experts." edia literacy lesson plans." uiding questions, exercises and checklists for deconstructing media messages.